Testing for hypersensitivity to seminal fluid-free spermatozoa. (1st June 2013) - Carroll, Michael; Horne, Gregory; Antrobus, Richard; Fitzgerald, Cheryl; Brison, Daniel; Helbert, Matthew
Abstract: Hypersensitivity to human semen (HHS) is an increasingly reported condition with symptoms manifested locally and systemically, which in some cases may result in anaphylaxis. This report describes four cases of HHS all with positive allergy skin prick tests to partner's whole semen. None of the patients elicited a response to seminal fluid-free washed spermatozoa. In cases of high risk of anaphylaxis, we recommend avoiding exposure to semen. By carrying out an allergy skin prick test on seminal fluid-free washed spermatozoa, the risk of immunogenic reaction to the spermatozoa could be eliminated.